Students’ Perception toward Implementation of Metacognitive Strategy in Higher Education - Novitasari S.Pd., M.Pd.; Nur Mafissamawati Sholikhah (Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Kadiri, 2021)
Metacognitive strategy is described as a thinking strategy of gaining knowledge and comprehension by knowing what students know and what they do not know. Since college students struggle to be successful in their study, they should have an awareness of applying this strategy in learning, so it can empower them to think about their own thinking process, enhance their control over their learning, and increase their autonomy to reach the goals. Therefore, teachers should consider incorporating metacognitive strategies in designing a lesson plan. This study aims to investigate the students’ perception toward metacognitive strategies used in class. It was done in two classes in D3 English Department. The participants consist of 49 students. Data was gained from distributing questionnaire to students after metacognitive strategies was applied in the class. There are two types of data, quantitative and qualitative data. The quantitative data was analysed using descriptive analysis, the qualitative data was described in depth analysis and summarized. The results found that most of the students had positive perception toward metacognitive strategies in the class. However, they found some challenges in implementing the strategies in their study.